2020
DOI: 10.1093/intqhc/mzaa166
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis: international variation in PET-CT service provision in oncology—an International Cancer Benchmarking Partnership study

Abstract: Objective To explore differences in position emission tomography-computed tomography (PET-CT) service provision internationally to further understand the impact variation may have upon cancer services. To identify areas of further exploration for researchers and policymakers to optimize PET-CT services and improve the quality of cancer services. Design Comparative analysis using data based on pre-defined PET-CT service metric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The access to more specialised staging modalities such as positron emission tomography (PET) scans, are variable between and even within jurisdictions and may influence the patient's final stage staging. [45] While, for the purpose of comparison, we used the SEER system to compare stage-specific survival estimates across countries, it should be noted that TNM remains the preferred staging classification, as it reflects patients' groupings in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…The access to more specialised staging modalities such as positron emission tomography (PET) scans, are variable between and even within jurisdictions and may influence the patient's final stage staging. [45] While, for the purpose of comparison, we used the SEER system to compare stage-specific survival estimates across countries, it should be noted that TNM remains the preferred staging classification, as it reflects patients' groupings in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…These include differences in the content of national clinical guidelines, or their implementation, or both; variable constraints in health-care professional capacity and the availability of treatment facilities; variation in professional culture and norms towards more or less conservative management; the variable extent of differences in clinical practice between providers or hospital teams within the same country; the differences in patient preferences and expectations of cancer care; the geographical location of treatment centres in relation to population residence; variable research infrastructure that could enable access to clinical trial protocols; and differences in the availability and content of national cancer control strategies, which might all be contributing to interjurisdictional differences in chemotherapy use. 6,7,22,23,30 In our study, interjurisdictional variation in time-tochemotherapy was generally smaller compared with variation in use. Artefactual causes of such variation are unlikely among patients identified as having received chemotherapy.…”
Section: Discussionmentioning
confidence: 43%
“…The study forms part of the International Cancer Benchmarking Partnership, a collaboration of clinicians, policy makers, researchers, and data experts in seven countries (Australia, Canada, Denmark, Ireland, New Zealand, Norway, and the UK), seeking to explain cancer survival differences between high-income countries with comprehensive cancer registries, similar health system expenditure, and universal health care, to help improve cancer care and outcomes globally. [5][6][7]…”
Section: Introductionmentioning
confidence: 99%
“…Although the UK guidelines promote FDG PET/CT for the visualisation of MPNSTs, other systemic factors may hamper its use. The UK has fewer PET/CT machines, 0.08 per 100,000 people [ 74 ], in comparison to 0.12 in Germany [ 75 ]. The relative scarcity of PET/CT scanners in the UK may underlie the comparative lower proportion of studies involving PET/CT scans from the UK, as shown in our study.…”
Section: Discussionmentioning
confidence: 99%